PENGEMBANGAN KAIN ENDEK SEBAGAI PRODUK PENUNJANG PARIWISATA BUDAYA DI BALI - Ni Made Ariani (Institut Pariwisata dan Bisnis Internasional, 2019)
Bali Island as a tourist destination is known for its natural beauty and cultural uniqueness. The uniqueness and characteristics of Balinese culture are very attractive to both domestic and foreign tourists. This makes Bali continue to explore and develop the potential of culture in the middle of society. The development is carried out to support cultural tourism as a superior program. In the development of cultural tourism, traditional fabrics have not also received attention through development programs. One of the traditional Balinese cloths that continuing to be developed is endek cloth. Endek fabric is a traditional fabric with its type of ikat. Previously endek cloth was widely used as clothing in Balinese religious rituals. The development of endek cloth as a supporting product for cultural tourism in Bali were made this fabric renewed and adjusted to the interests of tourists along the times. The aims of this study is to develop endek cloth with using qualitative methods. The theory that will be used is the theory of commodification and social practice theory. The results of the study include (1) the specialty of endek cloth as a supporting product for cultural tourism in Bali, (2) the process of developing endek cloth untill now, (3) Analysis of the development of endek cloth as a supporting product for cultural tourism both internal and external.